Sustainable (Post-)Pandemic Cities? Contested Forms of Knowledge in Urban Transformation. - Mölders, Tanja; Levin-Keitel, Meike (RWTH Aachen University, 2021)
For over a year, the COVID-19 pandemic is preoccupying scientists, politicians and each and every one of us in our professional and private lives. In this process, the spatial implications of the crisis soon became clear: named in terms like social distancing or the uneven affectedness of COVID-19 in different neighbourhoods. However, it remains complex to evaluate spatial implications in detail and derive actions for future urban design. Very quickly, voices were raised that see the crisis as an opportunity for transformation and assume that urban life after COVID-19 will be more sustainable. This article argues that a sustainable development will not occur per se, but like all transformation processes will be accompanied by conflicting goals within the sustainability discourse that can be understood as spatial conflicts. We therefore propose a systematic examination of system, target and transformation knowledge and consider this on the spatial level in order to open up analytical and designing perspectives. The paper ends with proposals for spatially informed policies, polities and politics towards more sustainable (post-)pandemic cities.
Keywords: Nachhaltige Stadtentwicklung; Freiraumnutzung; Transformation; Krisensituation; Soziale Ungleichheit; Raumnutzungskonzept; Sozialökologie; Nachhaltigkeit; Corona-Krise